2011
DOI: 10.28945/1476
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Mini Food E-additive Database for Mobile Telephones

Abstract: Our project has developed an application for mobile telephones to provide a catalogue of Enumbers and E-names: the food additives widely known as "E-numbers". Our application, the MIni Food E-Additive Database (MIFED) provides a user interface that is friendly and easy to use. To achieve our main goal of platform independence we applied the JAVA programming language to implement our software. Thus, based on JAVA our software can run on a very wide range of mobile devices. The development process of the softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…Az Ausztriában dolgozók jellemzőit és az ausztriai munkavállalás motivációit vizsgáló kismintás kutatások (például Kovács-Sipos 2020;Horváth 2019;Projactive Consulting Kft. 2018;EMPIRICA 2012;Lechner et al 2010;Hárs et al 2009;Hardi 2005;Sik 1999) mindegyike a hazainál jóval magasabb kereseti lehetőséget azonosította elsőszámú vonzó tényezőként, de emellett (vagy ezzel átfedésben) olyan motiváló tényezők is megjelentek, mint a tanulás/nyelvtanulás és a szakmai fejlődés lehetősége, illetve a külföldi élet megtapasztalása, a kíváncsiság vagy a kalandvágy, azonban ezek a motiváló tényezők a gyermeküket "hátrahagyó" szülők esetében egyáltalán nem azonosíthatók. Továbbá ezekben a kutatásokban, noha tudhatjuk, hogy az ausztriai fizetés a legfőbb "csábító", annak kontrasztjáról kevésbé esik szó: nem tudjuk, hogy arra kezdetben az álmok megvalósítása, előrelépés vagy éppen a túlélés, az "egyik hónapra a másikra élés" körforgásából való kikerülés miatt volt-e szükség.…”
Section: öSszegzés éS Következtetésekunclassified
“…Az Ausztriában dolgozók jellemzőit és az ausztriai munkavállalás motivációit vizsgáló kismintás kutatások (például Kovács-Sipos 2020;Horváth 2019;Projactive Consulting Kft. 2018;EMPIRICA 2012;Lechner et al 2010;Hárs et al 2009;Hardi 2005;Sik 1999) mindegyike a hazainál jóval magasabb kereseti lehetőséget azonosította elsőszámú vonzó tényezőként, de emellett (vagy ezzel átfedésben) olyan motiváló tényezők is megjelentek, mint a tanulás/nyelvtanulás és a szakmai fejlődés lehetősége, illetve a külföldi élet megtapasztalása, a kíváncsiság vagy a kalandvágy, azonban ezek a motiváló tényezők a gyermeküket "hátrahagyó" szülők esetében egyáltalán nem azonosíthatók. Továbbá ezekben a kutatásokban, noha tudhatjuk, hogy az ausztriai fizetés a legfőbb "csábító", annak kontrasztjáról kevésbé esik szó: nem tudjuk, hogy arra kezdetben az álmok megvalósítása, előrelépés vagy éppen a túlélés, az "egyik hónapra a másikra élés" körforgásából való kikerülés miatt volt-e szükség.…”
Section: öSszegzés éS Következtetésekunclassified
“…This acid was first isolated from the leaves of Rosmarinus officinalis, and it belongs to the hydroxycinnamic group, although it has been reported in several plant species [103]. Research has been reported showing its potential as an antiallergic, antimicrobial, antidepressant, antidiabetic, and antiinflammatory, and anticarcinogenic, nephroprotective, cardioprotective, hepatoprotective, and neuroprotective properties have also been associated with this compound, mainly due to its antioxidant potential [104,105].…”
Section: Compound Identification By Uhplcmentioning
confidence: 99%